Perilaku Kewirausahaan pada Usaha Mikro Kecil (UMK) Tempe di Bogor Jawa Barat - Tita Nursiah; Nunung Kusnadi; Burhanuddin Burhanuddin (Jurnal Agribisnis Indonesia, 2015)
Micro and small enterprises (MSE) is a dominant business form in Indonesia with the percentage up to 90%. However, there is a tendency that the entrepreneur is identified to large scale of business. The purpose of this study were (1) identify the characteristics of entrepreneurs in MSE industry (2) analyze the effect of entrepreneurial characteristics and the business climate for entrepreneurial behavior (3) analyze the effect of entrepreneurial behavior on its performance. Purposive sampling technique was applied to select 121 respondent. Structural Equation Modelling (SEM) was used to estimate entrepreneurial behavior. The results of this study showed that entrepreneurial characteristics was found on the MSE, furthermore  stronger entrepreneurial characteristics was found on the large scale production. There is a positive and significant relationship between entrepreneurial characteristics and the business climate for entrepreneurial behavior. Entrepreneurial characteristics was influencing the most on the behavior of entrepreneurs. In addition entrepreneurial behavior was also positive and significant influence on its business performance. Thus, this study confirmed that entrepreneurial behavior was also found in small businesses, not only in large enterprises.